A Room‐Temperature High‐Conductivity Metal Printing Paradigm with Visible‐Light Projection Lithography. (23rd November 2018) - Yang, Xingyun; Sun, Mo; Bian, Yinxu; He, Ximin
Abstract: Fabricating electronic devices require integrating metallic conductors and polymeric insulators in complex structures. Current metal‐patterning methods such as evaporation and laser sintering require vacuum, multistep processes, and high temperature during sintering or postannealing to achieve desirable electrical conductivity, which damages low‐temperature polymer substrates. Here reports a facile ecofriendly room‐temperature metal printing paradigm using visible‐light projection lithography. With a particle‐free reactive silver ink, photoinduced redox reaction occurs to form metallic silver within designed illuminated regions through a digital mask on substrate with insignificant temperature change (<4 °C). The patterns exhibit remarkably high conductivity achievable at room temperature (2.4 × 10 7 S m −1, ≈40% of bulk silver conductivity) after simple room‐temperature chemical annealing for 1–2 s. The finest silver trace produced reaches 15 µm. Neither extra thermal energy input nor physical mask is required for the entire fabrication process. Metal patterns were printed on various substrates, including polyethylene terephthalate, polydimethylsiloxane, polyimide, Scotch tape, print paper, Si wafer, glass coverslip, and polystyrene. By changing inks, this paradigm can be extended to print various metals and metal–polymer hybrid structures. This method greatly simplifies the metal‐patterning process and expands printability and substrate materials, showing huge potential in fabricating microelectronics with one system. Abstract : A facile ecofriendly room‐temperature metal printing paradigm using visible‐light projection lithography is reported. Remarkably high electrical conductivity is achieved after a room‐temperature chemical annealing for 1–2 s. This paradigm can be extended to print various metals and metal–polymer hybrid structures through changing inks. This method simplifies the metal‐patterning process, showing huge potential in fabricating microelectronics with one system.